1998
DOI: 10.1177/101269098033001003
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Class and the Construction of Masculinity in Professional Sailing

Abstract: Although the America's Cup, sailing's most prestigious international race, is nearly 150 years old, it was not until 1995 that the first women competed in it. Using feminist theory, it is suggested that female athletes have been barred from competition because sport has been constructed on the basis of men's rather than women's physical abilities. In particular, the unnecessary structuring of the crew position of grinder to emphasize upper-body strength has largely excluded women from a sport that does not inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…This appears to relate to the profile of the sport associated with the event. Competitive sailing has been critiqued as a traditionally masculine sport (Crawley, 1998), while equestrian event participants are predominantly female (British Eventing, 2009). Unlike the other three events at which volunteers were sampled, it appears the Equine WA event attracted volunteers whose skills were transferable from their current or past work roles.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to relate to the profile of the sport associated with the event. Competitive sailing has been critiqued as a traditionally masculine sport (Crawley, 1998), while equestrian event participants are predominantly female (British Eventing, 2009). Unlike the other three events at which volunteers were sampled, it appears the Equine WA event attracted volunteers whose skills were transferable from their current or past work roles.…”
Section: Resultsmentioning
confidence: 99%
“…While there have been studies undertaken into yacht chartering (Lett, 1983;Linington, 1998;Richens, 1992), this is essentially a different activity as the charters are usually short term in nature and the vessel is owned by someone else. Further, studies of the lived experiences of women involved in racing sailing vessels are also limited (e.g., Bricknell, 1999;Crawley, 1998). Although there are some similarities between the lived experiences of racing and cruising women, the nature of the two activities is different in terms of purpose, time, distance, ownership of vessels, monitoring procedures, as well as support structures.…”
Section: Introductionmentioning
confidence: 97%
“…It is more common to find research on women in male-dominated sports (Abrahamsen, et al, 2007;Banet-Weiser, 1999;Bricknell, 1999;Crawley, 1998), gender inequities in leisure time (Bittman & Wajcmac, 2000;Henderson & Allen, 1991;Kaczynski & Henderson, 2007) or gendered sports coverage (Eastman & Billings, 1999;Koivula, 1999;McDaniel et al, 2007;McGinnis et al, 2003;Messner, Dunbar, & Hunt, 2000) than studies exploring the social context of women in golf (Haig-Muir, 2000;McGinnis, et al, 2005;Pyles, 2007).…”
Section: Downloaded By [George Washington University] At 18:26 03 Febmentioning
confidence: 96%
“…Gendered sports participation has been a topic of interest for many authors, who have identified discrepancies in various areas: sports participation and physical education (Koivula, 1995;Lensky, 1991;Matteo, 1986), elite sports (Abrahamsen, Roberts, & Pensgaard, 2007), recreational sports (Carroll & Alexandris, 1997), basketball (Banet-Weiser, 1999), professional sailing (Bricknell, 1999;Crawley, 1998), the Olympics (Eastman & Billings, 1999), skiing , football (K. , motorcycling , tennis (Thomsson, 1999), parks and recreation (Kaczynski & Henderson, 2007), and golf (Callan & Thomas, 2004Haig-Muir, 2000;Pyles, 2007). Borsay (2006) clarified that "sport is often taken to be a recreation which is biologically male orientated, with its emphasis upon strength, competition, and combat.…”
Section: Gender In Sportsmentioning
confidence: 99%